IDENTIFIKASI PENYEBAB KEMATIAN DAN KEKERDILAN PADA AYAM RAS PEDAGING DI KELOMPOK PETERNAK MUARA SELAYAR DESA PIJOT KECAMATAN KERUAK KABUPATEN LOMBOK TIMUR - Made Sriasih; Sulaiman Ngongu Depamede; Wayan Wariata; Muhamad Ali; Anwar Rosyidi; Aini Aini (Universitas Mataram, 2023)
Success in broiler farming depends on several factors, namely feed, day-old chick (DOC), poultry management, and disease attacks. The Muara Selayar broiler farmer group in Pijot village in the Keruak sub-district of East Lombok is one of the non-industrial poultry farmers. The problems faced by the Muara Selayar farmer group are the mortality rate of DOC, which reached 7.4% (above the 5% threshold), and stunting syndrome. This community service activity aimed to identify the causes of the problems faced by the group so that losses experienced by farmers could be minimized. This community service activity was carried out through direct identification of dead chickens (post-mortem identification), surveys, and discussions. Based on the identification results, the cause of death of chickens in the Muara Selayar group was coccidiosis, characterized by reddish feces and bleeding in the cecum. Stunting syndrome in livestock is mainly caused by poor quality (grade) of seeds from the partners. The results of the discussion activities conducted with the farmers showed that they need bargaining power with partners about the quality of the DOC, so it is necessary to have special communication with partners who cooperate with them. Farmers must pay attention to good husbandry practices such as sanitizing flocks and the surrounding environment and treating livestock with safe materials that do not cause drug residues. From this community service activity, it can be concluded that coccidiosis was the cause of the death of chickens in the Muara Selayar farmer group. However, other poultry diseases such as Pullorum, ND, and CRD should receive attention because they often appear during the rearing period based on farmer reports. Stunting syndrome is mainly caused by low DOC quality.